2020
DOI: 10.1177/0269881120936468
|View full text |Cite
|
Sign up to set email alerts
|

Blockade of D3 receptor prevents changes in DAT and D3R expression in the mesolimbic dopaminergic circuit produced by social stress- and cocaine prime-induced reinstatement of cocaine-CPP

Abstract: Background: Cocaine may cause persistent changes in the brain, which are more apparent in DA transporter (DAT) and DA receptor availability within the nucleus accumbens (NAc). On the other hand, the DA D3 receptor (D3R) has emerged as a promising pharmacotherapeutic target for substance use disorders. Aims: This study aims to assess the impact of selective D3R antagonism on DAT and D3R after reinstatement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
28
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(34 citation statements)
references
References 77 publications
6
28
0
Order By: Relevance
“…In accordance with our previous studies [25,26], this work shows that the blockade of D3R inhibited the reinstatement of cocaine-CPP induced by social stress but was not able to prevent the reactivation of cocaine-CPP elicited by a drug-prime, pointing out that D3R modulates differently the reinstatement of drug-seeking behaviours depending upon the stimulus that triggers relapse.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…In accordance with our previous studies [25,26], this work shows that the blockade of D3R inhibited the reinstatement of cocaine-CPP induced by social stress but was not able to prevent the reactivation of cocaine-CPP elicited by a drug-prime, pointing out that D3R modulates differently the reinstatement of drug-seeking behaviours depending upon the stimulus that triggers relapse.…”
Section: Discussionsupporting
confidence: 91%
“…Although not significantly, we observed that D3R levels tended to increase in the BLA of mice that reinstated cocaine-CPP under both conditions. These data parallel with recent results of our laboratory revealing a significant enhancement of D3R expression in the NAc of mice that reinstated cocaine-CPP after a drug prime or social defeat [26], and are in line also with studies that reported increased D3R in the reward system of human cocaine addicts and mice conditioned to cocaine cues [54,55]. This augment has been related to the association of cocaine effects with environmental contexts and not to the drug of abuse per se [55].…”
Section: The Administration Of Sb-277011-a Blocked the Reduction Of Psupporting
confidence: 91%
See 3 more Smart Citations